The impact of tranexamic acid on administration of red blood cell transfusions for resection of colorectal liver metastases. Issue 2 (February 2021) - Jaffer, Alisha A.; Karanicolas, Paul J.; Davis, Laura E.; Behman, Ramy; Hanna, Sherif S.; Law, Calvin H.; Coburn, Natalie G.; Roke, Rachel; Lemke, Madeline; Beyfuss, Kaitlyn A.; Hallet, Julie
Abstract: Background: Red blood cell transfusions (RBCT) remain a concern for patients undergoing hepatectomy. The effect of tranexamic acid (TXA), an anti-fibrinolytic, on receipt of RBCT in colorectal liver metastases (CRLM) resection was examined. Methods: Hepatectomies for CRLM over 2009–2014 were included. Primary outcome was 30-day receipt of RBCT. Secondary outcomes were 30-day major morbidity (Clavien-Dindo III-V) and 90-day mortality. Multivariable modelling examined the adjusted association between TXA and outcomes. Results: Of 433 included patients, 146 (34%) received TXA. TXA patients were more likely to have inflow occlusion (41.8% vs. 23.1%; p < 0.01) and major hepatectomies (56.1% vs. 45.6%; p = 0.0193). TXA was independently associated with lower risk of RBCT (Relative risk (RR) 0.59; 95% confidence interval (95%CI): 0.42–0.85), but not with 30-day major morbidity (adjusted RR 1.02; 95%CI: 0.64–1.60) and 90-day mortality (univariable RR 0.99; 95%CI: 0.95–1.03). Conclusion: Intraoperative TXA was associated with a 41% reduction in risk of 30 -day receipt of RBCT after hepatectomy for CRLM. This finding is important to potentially improve healthcare resource allocation and patient outcomes. Pending further evidence, intraoperative TXA may be an effective method of reducing RBCT in hepatectomy for CRLM.